PENDEKATAN DUNIA KETIGA TERHADAP HUKUM INTERNASIONAL: PENGARUH INSTITUSI INTERNASIONAL TERHADAP KEBIJAKAN DI INDONESIA - Darma Putra, I Putu Aditya (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
This article examines how international institutions, particularly the World Trade Organization (WTO), the International Monetary Fund (IMF), and the World Bank (WB), influence the economic policies of Indonesia, both through loans and rulings issued by these institutions. The analysis employs a Third World Approach to International Law, drawing upon interdisciplinary perspectives to conduct a socio-legal study. The findings reveal that international institutions play a significant role in shaping general principles of international economics and governing global economic relations to facilitate the accommodation of capital from developed countries. As a result, Third World countries, including Indonesia, are compelled to adopt the same laws without considering their level of development.